‫أثر الاشهار‬ ‫الخارجي‬ ‫على‬ ‫الصورة‬ ‫الذهنية‬ ‫للزبون‬ ‫في‬ ‫عينة‬ ‫من‬ ‫الوكالات‬ ‫السياحية ‬‫بوالية‬ ‫سوق‬ ‫أهراس‬ - أسامة ‫خدايجية ‬; ‬‫مهدي ‫سمارة ‬ (My University, 2017)
The purpose of this study was to highlight the role of external advertising in its dimensions: mental and emotional, and its impact on the mental image of the customer, in its three dimensions: the cognitive dimension, the behavioral dimension, the emotional dimension. To achieve this goal, a study in the field was conducted on advertising banners of the three tourism agencies active in the state of Souq Ahras: (Al-Sanabel Agency and Al- Najah Agency and medjerda Agency). a questionnaire survey was designed for this purpose. It was distributed to the sample of the study, which included the current customers of the previously mentioned agencies, which consisted of 75 customers. The Spss19 program was taken into account to realize the process of data entry and analysis, it was also used to build theories and come up with results. Finally, the study concluded that external advertising affects the mental image of a client in all its dimensions: cognitive, behavioral and emotional, and the nature of this relationship is somewhat weak.